Analisis Visual Desain Cover Novel-novel Karya Boy Candra - Franciscus Xaverius Langga; Sumarwahyudi; Abdul Rahman Prasetyo (Universitas Negeri Malang, 2021)
Abstract: Novel is a work of fiction that is printed like a book and has a cover. Novel cover is one element that can increase the purchasing power of its readers. Therefore, the cover of the novel is designed in an attractive manner, including the novels by Boy Candra which become the identity of the author and the novel is also one of the reasons why these novels become best sellers. Some elements that can compose a cover design are illustration, colour, and typography. The research objective to be achieved is to determine the visual design of the cover of Boy Candra's novels, which includes several elements, namely illustrations, colours, and typography. This study uses a qualitative descriptive method using observation and documentation as its data collection instruments. The result of analysis showed that the cover design of Boy Candra’s novel made use of achromatic colour that looks simple, elegant, mysterious, and dark. In addition, the writing design on the cover uses a consistent type of typography, for example on the nameplate/logo, synopsis, masthead, and also headlines that use script and cursive fonts. Keywords: Visual Analysis, Illustration, Colour, Typography, Novel Cover Abstrak: Novel merupakan karya fiksi yang dicetak seprti sebuah buku dan memiliki cover. Cover novel merupakan salah satu elemen yang dapat meningkakan daya beli para pembacanya. Oleh karena itu, cover novel didesain secara menarik, termasuk novel-novel karya Boy Candra yang menjadi identitas pengarang dan novelnya pun menjadi salah satu alasan novel-novel tersebut menjadi best seller. Beberapa unsur yang dapat menyususn sebuah desain cover yaitu ilustrasi, warna,dan tipografi. Tujuan penelitian yang hendak dicapai oleh adalah untuk mengetahui desain visual cover novel-novel Boy Candra, yang meliputi beberapa hal yaitu ilustrasi, warna, dan tipografi. Penelitian ini menggunakan metode deskriptif kualitatif dengan instrument penelitian obseervasi dan dokumentasi. Dengan menggunakan metode dan instrumen penelitian tersebut, dapat disimpulkan bahwa desain cover warna yang digunakan pada cover adalah warna akromatik, terlihat simple, elegan, misterius, sedih. Selain itu, desain tulisan pada cover menggunaan jenis tipografi yang konsisten pada cover novel karya Boy Candra, contohnya pada nameplate/logo, sinopsis, masthead, dan juga headline yang menggunakan font script and cursive. Kata kunci: analisis visual, ilustrasi, warna, tipografi, cover novel